Answer to ECG Quiz no. 7 - Okreglicki, A. (SA Heart Journal, 2017)
Before analyzing the ECG in detail, it is worth making a general comment about the association between ongoing comatose state and cardiac rhythm in this and other patients. No matter what the rhythm may be, with normal rate, fast tachycardia or even severe bradycardia, if there is a cardiac output as evidenced by a reasonable blood pressure with peripheral perfusion, an ongoing state of coma cannot be attributed to the cardiac rhythm at that time. Yes, an arrhythmia may have caused transient syncope (and even occasionally seizures) but the mechanism would have been transient hypotension insuffi cient to maintain cerebral perfusion.